TEACHERS’ STRATEGIES AND CHALLENGES IN TEACHING ONLINE SPEAKING ACTIVITIES - Jusak Patty; Faneshya Mariana Bilung (University of Muhammadiyah Malang, 2023)
This study examines the strategies used by vocational education teachers to teach speaking skills online. Specifically, it focuses on English teachers Vocational High School in Ambon and their challenges in implementing these strategies. The study aims to provide practical insights for teaching speaking skills in online vocational high schools and recommend teacher professional development. The research design involves qualitative research methods, including interviews with two English teachers who teach third-grade Nursing students. The interviews were conducted to gather information on the teachers’ strategies and challenges in teaching speaking skills online. The collected data were analyzed using qualitative analysis techniques. The findings indicate that the teachers used dialogue, describing pictures, and drilling as strategies for teaching speaking skills online. Teachers also faced technical and pedagogical challenges in implementing these strategies. Technical challenges included internet reliability, limited device access, and teachers’ technological proficiency. Pedagogical challenges involved limited student-teacher interaction, reduced student engagement, and the asynchronous nature of online platforms. This study contributes valuable insights into teaching speaking skills in online vocational high schools. The findings can inform instructional practices and guide teacher professional development programs to enhance online speaking instruction.